Cave growth mechanism and surface subsidence in a structurally complex block cave: P0 case study - Bayar, E; Ooi, J; Naranzorig, Z; Mendbayar, D; Ulziijargal, M-E; Khurmyet, B; Brunton, I (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
This paper examines cave propagation and surface subsidence at the Panel 0 Block Cave, Oyu Tolgoi, developed within a deep (~1,300 m) and structurally complex rock mass. Cave growth was strongly controlled by major faults, persistent discontinuities, and low-strength fractured zones, evolving from stress-driven yielding at depth to structurally guided propagation upward, reaching the surface in ~36 months. Measurable subsidence began in Q1 2025, with its geometry and rates reflecting pronounced structural anisotropy. Integrated monitoring data and numerical modelling were used to reconstruct cave evolution and interpret the governing failure mechanisms.
Keywords: cave propagation mechanism; plug subsidence; rock mass dilation; Panel 0